Hierarchical pore MOFs-based composite phase change material as well as preparation method and application thereof

By introducing phase change materials into MOFs materials and controlling the porous structure, the problem of temperature rise during the adsorption process is solved, the adsorption efficiency and desorption efficiency are improved, and the life of the adsorbent is extended.

CN119327425AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310890076.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The temperature rise problem caused by poor thermal conductivity during the adsorption process of existing adsorption materials limits the adsorption efficiency and the efficiency of the desorption process.

Method used

Develop a multi -grade MOFS base composite phase variable material. By introducing phase -changing materials in MOFS materials and controlling the structure of micro -holes, metors, and large holes to achieve the storage and release of adsorption heat.

Benefits of technology

It improves the adsorption efficiency and desorption process efficiency, reduces the temperature rise of the adsorption bed, and extends the life of the adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327425A_ABST
    Figure CN119327425A_ABST
Patent Text Reader

Abstract

The invention relates to the field of adsorption materials, and discloses a hierarchical porous MOFs-based composite phase change material as well as a preparation method and application thereof. The MOFs-based composite phase change material comprises a hierarchical porous MOFs material with micropores, mesopores and macropores at the same time, and a phase change material loaded in the macropores of the hierarchical porous MOFs material. The prepared hierarchical-pore MOFs-based composite phase change material takes a hierarchical-pore MOFs material as a matrix, has higher specific surface area and pore volume, respectively has a certain number of micropore, mesopore and macropore structures, and fully develops the functions of pore channels with different sizes, in the process of adsorbing VOCs by the micropores, the mesopores are beneficial to mass transfer of fast adsorbate and increase of adsorption rate, and the adsorption rate is increased. The phase change material in the macropores can store and adsorb heat to inhibit the temperature rise of the bed layer and improve the adsorption efficiency of the bed layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adsorption materials, and in particular to a multi-level porous MOFs-based composite phase change material and a preparation method and application thereof. Background Art

[0002] In the past few decades, traditional porous materials such as molecular sieves, silica gel and activated carbon have been widely used in the fields of gas selective adsorption, gas storage, gas separation and purification. Compared with traditional adsorption materials such as activated carbon and molecular sieves, metal organic framework compounds (MOFs) have the advantages of high specific surface area, high porosity and diverse skeleton structure, which makes them have broad application prospects in the fields of gas storage and separation. So far, most of the reported MOFs have microporous structures, which leads to very slow diffusion and mass transfer rates of adsorbed molecules, thus limiting the wide application of MOFs materials in the field of gas adsorption.

[0003] In addition, a large number of studies have confirmed that gas molecules release or absorb heat during adsorption or desorption on solid surfaces. However, the thermal conductivity of adsorption materials such as activated carbon, molecular sieves, silica gel and MOFs is relatively poor. The heat generated by adsorption during the adsorption process accumulates, resulting in a large temperature rise in the entire adsorption bed, which in turn causes the temperature of the gas-solid system to rise, seriously reducing the gas adsorption capacity. In the desorption process, energy needs to be absorbed, which causes the bed temperature to drop. The temperature drop will have an adverse effect on the desorption process, causing part of the gas, especially the heavy components, to remain in the adsorbent, affecting the release capacity and life of the adsorbent. By adding thermal conductive materials such as graphene and carbon nanotubes to activated carbon and MOFs, the thermal conductivity of the composite phase change material can be improved, so that the heat generated by the adsorption bed can be quickly diffused into the environment, thereby alleviating the temperature rise of the bed. However, this method causes heat to be lost in vain and the energy utilization rate is not high. In addition, the price of thermal conductive materials is high, which makes the cost of adsorption materials also high. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems in the prior art, such as low material adsorption efficiency and difficulty in adsorbing light hydrocarbons, caused by the adsorption heat effect, and to provide a multi-level porous MOFs-based composite phase change material and its preparation method and application.

[0005] In order to achieve the above-mentioned objectives, the present invention provides a multi-level porous MOFs-based composite phase change material on the one hand, wherein the multi-level porous MOFs-based composite phase change material includes a multi-level porous MOFs material having micropores, mesopores and macropores at the same time, and a phase change material loaded in the macropore channels of the multi-level porous MOFs material.

[0006] Preferably, the ratio of the micropore volume, mesopore volume and macropore volume of the hierarchical porous MOFs material is 1-4:1-2:1.

[0007] Preferably, the specific surface area of ​​the multi-level porous MOFs material is 600-1700m 2 / g.

[0008] Preferably, the phase change material is selected from one or more of polyols, fatty acids, linear alkanes and paraffins.

[0009] Preferably, the polyols are polyethylene glycol and / or neopentyl glycol.

[0010] Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid.

[0011] Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned multi-level porous MOFs-based composite phase change material, the preparation method comprising the following steps:

[0013] (1) mixing a metal salt with water to obtain a metal salt solution;

[0014] (2) mixing the template, the organic ligand and the organic solvent to obtain an organic phase solution;

[0015] (3) mixing the metal salt solution with the organic phase solution, and then reacting, separating the solid and the liquid after the reaction, and washing and activating the obtained solid in sequence to obtain a hierarchical MOFs material;

[0016] (4) Mixing the phase change material with an organic solvent to obtain an organic phase change material solution, and immersing the multi-level porous MOFs material in the organic phase change material solution.

[0017] Preferably, the metal salt is selected from one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate, zirconium chloride and nickel chloride hexahydrate.

[0018] Preferably, the content of metal salt in the metal salt solution is 5-50 g / L.

[0019] Preferably, the template agent is selected from one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and N,N,N,N-tetramethylethylenediamine.

[0020] Preferably, the organic ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, 2,5-thiophenedicarboxylic acid and triethylenediamine.

[0021] Preferably, the organic ligand is selected from one or more of 2-aminoterephthalic acid, 2,5-thiophenedicarboxylic acid, trimesic acid, terephthalic acid and triethylenediamine.

[0022] Preferably, the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane.

[0023] Preferably, the content of the template in the organic phase solution is 10-80 g / L, and the content of the organic ligand is 30-150 g / L.

[0024] Preferably, the molar ratio of the metal salt, the template and the organic ligand is 1:0.03-1:1-2.

[0025] Preferably, in step (3), the reaction conditions include: temperature of 20-160° C., and time of 6-18 h.

[0026] Preferably, the reaction conditions include: temperature of 40-110° C. and time of 8-16 h.

[0027] Preferably, in step (3), the activation conditions include: temperature of 80-180° C., time of 1-24 h, and absolute vacuum of 20-80 kPa.

[0028] Preferably, the activation conditions include: temperature of 100-160° C. and time of 2-6 h.

[0029] Preferably, in step (4), the content of phase change material in the organic phase change material solution is 5-80 g / L.

[0030] Preferably, the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.05-0.5.

[0031] Preferably, in step (4), the immersion conditions include: time of 4-7 hours and temperature of 40-70°C.

[0032] A third aspect of the present invention provides an application of the above-mentioned multi-level porous MOFs-based composite phase change material in the adsorption of VOCs.

[0033] The present invention adjusts the uniform pore size of the traditional MOFs material with highly uniform pore size distribution, and provides a MOFs material with multi-level pore size, so that it has micropores, mesopores and macropores at the same time. The multi-level pore MOFs material is used as a phase change material carrier, and the phase change material is stored in the macropore channel. The adsorption heat is stored by means of the phase change process of the material, and the adsorption efficiency of the material is improved; the presence of the mesopore channel helps to accelerate the mass transfer rate of the MOFs material in the process of adsorbing VOCs; the micropore channel is used as the adsorption site of VOCs, which meets the demand for the composite material to have a higher adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a nitrogen adsorption isotherm curve of the hierarchical MOFs material of Example 1;

[0035] Figure 2 is a pore size distribution diagram of the multi-level porous MOFs material of Example 1;

[0036] Figure 3 is a penetration adsorption curve of ethane by the multi-level porous MOFs material of Example 1;

[0037] Figure 4 is a pore size distribution diagram of the multi-level porous MOFs-based composite phase change material of Example 1;

[0038] Figure 5 is a penetration adsorption curve of ethane by the multi-level porous MOFs-based composite phase change material of Example 1;

[0039] Figure 6 is a penetration adsorption curve of ethane by the multi-level porous MOFs-based composite phase change material of Example 2;

[0040] Figure 7 This is a graph showing the penetration adsorption of ethane by the multi-level porous MOFs-based composite phase change material of Example 3. DETAILED DESCRIPTION

[0041] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0042] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0043] On the one hand, the present invention provides a multi-level porous MOFs-based composite phase change material, which includes a multi-level porous MOFs material having micropores, mesopores and macropores, and a phase change material loaded in the macropore channels of the multi-level porous MOFs material.

[0044] In the present invention, the multi-level porous MOFs-based composite phase change material comprises a multi-level porous MOFs material and a phase change material. The multi-level porous MOFs material has micropores, mesopores and macropores at the same time. The phase change material is loaded in the macropore channels of the multi-level porous MOFs material.

[0045] In the present invention, in order to make the hierarchical MOFs-based composite phase change material have better adsorption effect and self-temperature control characteristics, it is necessary to reasonably control the proportion of micropores, mesopores and macropores. In a preferred case, the ratio of the micropore volume, mesopore volume and macropore volume of the hierarchical MOFs material is 1-4:1-2:1, specifically 1:1:1, 2:1:1, 3:1:1, 4:1:1, 1:2:1, 2:2:1, 3:2:1 or 4:2:1.

[0046] Preferably, the specific surface area of ​​the multi-level porous MOFs material is 600-1700m 2 / g, specifically 600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g or 1700m 2 / g.

[0047] In the present invention, in order to ensure that the phase change materials are loaded in the macropore channels of the multi-level porous MOFs-based composite phase change material, it is preferred that the phase change materials are all macromolecular phase change materials. Further preferably, the phase change materials are selected from one or more of polyols, fatty acids, straight-chain alkanes and paraffins.

[0048] Preferably, the polyols are polyethylene glycol and / or neopentyl glycol.

[0049] Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid.

[0050] Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

[0051] In the present invention, when the phase change material contains paraffin, in order to ensure that the adsorption process can be controlled at a relatively low temperature, it is more appropriate to select paraffin with a phase change temperature of 30-50°C, and more preferably paraffin with a phase change temperature of 38°C.

[0052] The second aspect of the present invention provides a method for preparing the above-mentioned multi-level porous MOFs-based composite phase change material, the preparation method comprising the following steps:

[0053] (1) mixing a metal salt with water to obtain a metal salt solution;

[0054] (2) mixing the template, the organic ligand and the organic solvent to obtain an organic phase solution;

[0055] (3) mixing the metal salt solution with the organic phase solution, and then reacting, separating the solid and the liquid after the reaction, and washing and activating the obtained solid in sequence to obtain a hierarchical porous MOFs material;

[0056] (4) Mixing a phase change material with an organic solvent to obtain an organic phase change material solution, and immersing the multi-level porous MOFs material in the organic phase change material solution.

[0057] In the present invention, the metal salts are selected from soluble metal salts and / or slightly soluble metal salts.

[0058] Preferably, the metal salt is selected from aluminum chloride, aluminum chloride hexahydrate, aluminum nitrate, aluminum sulfate, aluminum acetate, ferric chloride, ferric chloride hexahydrate, ferric sulfate, ferric nitrate, ferric acetate, cupric chloride, cupric sulfate, cupric nitrate, cupric acetate, cupric acetate monohydrate, cupric sulfate pentahydrate, cupric nitrate trihydrate, chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, chromium nitrate nonahydrate, chromium chloride hexahydrate, zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium acetate, zirconium nitrate pentahydrate, nitrate One or more of the following: zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate monohydrate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, manganese sulfate monohydrate, manganese nitrate hexahydrate, and manganese acetate dihydrate.

[0059] Preferably, the metal salt is selected from one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate, zirconium chloride and nickel chloride hexahydrate.

[0060] Preferably, in step (1), the content of metal salt in the metal salt solution is 5-50 g / L, specifically 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L.

[0061] Preferably, the template is selected from one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), hexadecyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate and N,N,N,N-tetramethylethylenediamine.

[0062] Preferably, the organic ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, 2,5-thiophenedicarboxylic acid and triethylenediamine.

[0063] More preferably, the organic ligand is selected from one or more of 2-aminoterephthalic acid, 2,5-thiophenedicarboxylic acid, trimesic acid, terephthalic acid and triethylenediamine.

[0064] Preferably, in step (2), the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide (DMF), dichloromethane and 1,2-dichloroethane.

[0065] Preferably, in step (2), the content of the template in the organic phase solution is 10-80 g / L, and the content of the organic ligand is 30-150 g / L.

[0066] In a specific embodiment, in step (2), the content of the template in the organic phase solution can be 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L or 80 g / L, and the content of the organic ligand in the organic phase solution can be 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L or 150 g / L.

[0067] In the preparation method described in the present invention, under preferred circumstances, the molar ratio of the metal salt, template and organic ligand is 1:0.03-1:1-2, wherein the organic ligand is more than the metal salt to ensure that after the multi-level porous MOFs material is generated, the unreacted organic ligand can be washed away with an organic solvent, while too much template will cause the quality of the multi-level porous MOFs material to be seriously reduced, so it is necessary to control the usage ratio of each raw material within the above range.

[0068] In a specific embodiment, the molar ratio of the metal salt, the template and the organic ligand can be 1:0.03:1, 1:0.04:1, 1:0.05:1, 1:0.06:1, 1:0.07:1, 1:0.08:1, 1:0.09:1, 1:1:1, 1:0.03:2, 1:0.04:2, 1:0.05:2, 1:0.06:2, 1:0.07:2, 1:0.08:2, 1:0.09:2 or 1:1:2.

[0069] In a preferred embodiment of the present invention, in step (3), the reaction conditions include: temperature of 20-160° C. and time of 6-18 h.

[0070] Further preferably, in step (3), the reaction conditions include: temperature of 40-110° C. and time of 8-16 h.

[0071] In a specific embodiment, in step (3), the reaction temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, and the reaction time can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h.

[0072] In step (3) of the present invention, the obtained solid can be washed with an organic solvent to remove unreacted metal salts, templates and organic ligands, etc. The organic solvent can be selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, preferably anhydrous ethanol is used for washing.

[0073] In step (3) of the present invention, there is no special requirement for the number of washings, and the unreacted metal salt, template agent, organic ligand, etc. can be removed.

[0074] In a preferred embodiment of the present invention, in step (3), the activation conditions include: temperature of 80-180° C., time of 1-24 h, and absolute vacuum of 20-80 kPa.

[0075] Further preferably, in step (3), the activation temperature is 100-160° C., and the activation time is 2-6 h.

[0076] In a specific embodiment, in step (3), the activation temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C, the activation time can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, and the absolute vacuum degree of activation can be 20kPa, 25kPa, 30kPa, 35kPa, 40kPa, 45kPa, 50kPa, 55kPa, 60kPa, 65kPa, 70kPa, 75kPa or 80kPa.

[0077] Preferably, in step (4), the organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, and is more preferably anhydrous ethanol.

[0078] In step (4) of the present invention, in order to ensure that the phase change materials are all loaded in the macropore channels of the multi-level porous MOFs-based composite phase change material, it is preferred that the phase change materials are all macromolecular phase change materials. Further preferably, the phase change materials are selected from one or more of polyols, fatty acids, straight-chain alkanes and paraffins.

[0079] Preferably, the polyols are polyethylene glycol and / or neopentyl glycol.

[0080] Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid.

[0081] Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

[0082] In the present invention, when the phase change material contains paraffin, in order to ensure that the adsorption process can be controlled at a relatively low temperature, it is more appropriate to select paraffin with a phase change temperature of 30-50°C, and more preferably paraffin with a phase change temperature of 38°C.

[0083] In a preferred embodiment of the present invention, in step (4), the content of phase change material in the organic phase change material solution is 5-80 g / L.

[0084] In a specific embodiment, in step (4), the content of phase change material in the organic phase change material solution can be 5 g / L, 15 g / L, 25 g / L, 35 g / L, 45 g / L, 55 g / L, 65 g / L, 75 g / L or 80 g / L.

[0085] Preferably, in step (4), the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.05-0.5, specifically 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5.

[0086] In a preferred embodiment of the present invention, in step (4), the immersion conditions include: a time of 4-7 hours and a temperature of 40-70°C.

[0087] In a specific embodiment, in step (4), the immersion time can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h or 7h, and the immersion temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.

[0088] In step (4) of the present invention, after the impregnation is completed, filtration is required, and the solid obtained by filtration is dried.

[0089] In the present invention, by controlling the dosage ratio of the hierarchical porous MOFs material to the organic phase change material and the impregnation conditions, a suitable hierarchical porous MOFs-based composite phase change material can be obtained.

[0090] In the present invention, the drying conditions include: temperature of 60-70° C. and time of 4-6 hours.

[0091] In a specific embodiment, the drying temperature can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, and the drying time can be 4h, 4.5h, 5h, 5.5h or 6h.

[0092] The multi-level porous MOFs-based composite phase change material prepared by the above-mentioned preparation method in the present invention contains 5-30 weight % of phase change material. In a specific embodiment, the content of phase change material in the multi-level porous MOFs-based composite phase change material can be 5 weight %, 10 weight %, 15 weight %, 20 weight %, 25 weight % or 30 weight %.

[0093] A third aspect of the present invention provides an application of the above-mentioned multi-level porous MOFs-based composite phase change material in the adsorption of VOCs.

[0094] In the present invention, under the action of a suitable template, the self-assembly of metal salts and organic ligands is restricted, the original periodic network structure is destroyed, and the addition amount of the template and the reaction conditions are controlled at the same time, so as to obtain a multi-level porous MOFs material having micropore, mesopore and macropore structures at the same time. The multi-level porous MOFs material has the characteristics of three-dimensional ordered interconnected structure, adjustable pore size, ultra-large specific surface area, etc., and can be used as a carrier of phase change material. On the basis of the multi-level porous MOFs material, the phase change material is introduced into the macropore channel. Compared with the traditional MOFs material, in the process of micropore adsorption of VOCs, the mesopore channels in the multi-level pores contribute to the diffusion of the adsorbate, accelerate the mass transfer rate, and improve the adsorption rate, while the phase change material in the macropores offsets the adsorption heat effect through phase change, which can control the temperature rise of the bed, thereby significantly improving the adsorption efficiency of the bed. Therefore, the multi-level porous MOFs material loaded with the phase change material has the function of storing adsorption heat, which can effectively reduce the temperature rise of the bed during the adsorption of VOCs.

[0095] The multi-level porous MOFs-based composite phase change material of the present invention has the characteristics of high phase change material loading rate, low bed temperature rise and fast adsorption rate, and can be used in the field of VOCs control, especially for adsorbing light hydrocarbons, such as ethane, propane and other small molecules. It has broad application prospects in the adsorption control of VOCs and has achieved good technical effects.

[0096] Compared with the prior art, the present invention has the following advantages:

[0097] (1) The present invention uses a template to synthesize a multi-level porous MOFs material, and the porous coordination polymer is distributed more evenly and densely on the surface.

[0098] (2) The synthesis method of the present invention is simple, avoiding cumbersome preparation processes and operating conditions, and is suitable for large-scale preparation and use. The synthesis of multi-level porous materials can be achieved by a one-step method, and a self-controlled temperature adsorption material can be obtained by a simple impregnation method, which has the prospect of large-scale production and application.

[0099] (3) The multi-level porous MOFs-based composite phase change material prepared by the present invention uses multi-level porous MOFs material as a matrix, has a high specific surface area and pore volume, has a certain number of micropores, mesopores and macropore structures, and fully develops the functions of pores of different sizes. In the process of microporous adsorption of VOCs, the mesopores are conducive to the mass transfer of the adsorbent and improve the adsorption rate, and the phase change material in the macropores can store adsorption heat to inhibit the temperature rise of the bed.

[0100] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0101] In the following examples, copper acetate monohydrate, triethylenediamine, zinc nitrate hexahydrate and aluminum chloride hexahydrate are all products of Shanghai Aladdin Biochemical Technology Co., Ltd., chromium nitrate nonahydrate, zirconium chloride, nickel chloride hexahydrate, trimesic acid, 2,5-thiophenedicarboxylic acid and 2-aminoterephthalic acid are all products of Shanghai McLean Biochemical Technology Co., Ltd., CTAB is a product of Beijing Inokai Technology Co., Ltd., terephthalic acid is a product of Shanghai Kaishu Chemical Technology Co., Ltd., n-octadecane is a product of Tianjin Xiens Biochemical Technology Co., Ltd., 38°C and 45°C phase change paraffin is a product of Shanghai Ruentropy New Energy Technology Co., Ltd., and anhydrous ethanol and DMF are products of China National Pharmaceutical Group Co., Ltd.

[0102] The room temperature below refers to 25℃.

[0103] Example 1

[0104] (1) adding 2.8 g of metal salt (copper acetate monohydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0105] (2) 3.1 g of the template (CTAB) and 3.8 g of the organic ligand (trimesic acid) were added to a beaker containing an organic solvent (anhydrous ethanol), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template was 26 g / L and the content of the organic ligand was 32 g / L);

[0106] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are added to a reaction bottle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.61:1.29), placed in an oil bath, and reacted at 40°C for 8 hours. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 100°C and an absolute vacuum of 40 kPa for 6 hours to obtain a multi-level porous MOFs material B1;

[0107] (4) Add 0.6 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 60 g / L), place 1.5 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.4), immerse at 40°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A1.

[0108] Example 2

[0109] (1) 3.1 g of metal salt (aluminum chloride hexahydrate) was added to a beaker containing water, and ultrasonicated at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt was 45 g / L);

[0110] (2) 3.6 g of template (CTAB) and 3.5 g of organic ligand (2,5-thiophenedicarboxylic acid) were added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template was 60 g / L and the content of the organic ligand was 58 g / L);

[0111] (3) adding the metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) into a reaction bottle (the molar ratio of the metal salt, template and organic ligand is 1:0.77:1.58), placing the reaction bottle in an oil bath, reacting at 100° C. for 9 h, obtaining a suspension after the reaction, and centrifuging the suspension after cooling to room temperature. The obtained solid was washed twice with anhydrous ethanol, and then the washed solid was placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 40 kPa for 4 h to obtain a hierarchical MOFs material;

[0112] (4) Add 0.6 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 60 g / L), place 2 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.3), immerse at 70°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A2.

[0113] Example 3

[0114] (1) adding 4 g of metal salt (chromium nitrate nonahydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 44 g / L);

[0115] (2) adding 2.6 g of template (CTAB) and 3.4 g of organic ligand (2-aminoterephthalic acid) into a beaker containing an organic solvent (anhydrous ethanol), and performing ultrasonication at room temperature to mix them uniformly to obtain an organic phase solution (the content of template is 50 g / L, and the content of organic ligand is 65 g / L);

[0116] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.71:1.88), placed in an oven, and reacted at 90° C. for 12 h. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 60 kPa for 4 h to obtain a multi-level porous MOFs material;

[0117] (4) Add 0.5 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 50 g / L), place 1.5 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.33), immerse at 60°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A3.

[0118] Example 4

[0119] (1) adding 2.5 g of metal salt (zinc nitrate hexahydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 30 g / L);

[0120] (2) 2.6 g of template (CTAB) and 1.9 g of organic ligand (terephthalic acid) were added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template was 60 g / L and the content of the organic ligand was 44 g / L);

[0121] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.84:1.36), placed in an oven, and reacted at 110° C. for 13 h. After the reaction is completed, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 140° C. and an absolute vacuum of 60 kPa for 6 h to obtain a multi-level porous MOFs material;

[0122] (4) Add 0.5 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 50 g / L), place 2 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.25), immerse at 50°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A4.

[0123] Example 5

[0124] (1) adding 1.2 g of metal salt (zirconium chloride) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0125] (2) 1.6 g of template (CTAB) and 1.1 g of organic ligand (terephthalic acid) were added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of template was 70 g / L and the content of organic ligand was 48 g / L);

[0126] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.85:1.29), placed in an oven, and reacted at 90° C. for 12 h. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated for 4 h at 120° C. and an absolute vacuum of 60 kPa to obtain a multi-level porous MOFs material;

[0127] (4) Add 0.3 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 37.5 g / L), place 3 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.1), immerse at 40°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A5.

[0128] Example 6

[0129] (1) adding 0.6 g of metal salt (nickel chloride hexahydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0130] (2) adding 0.8 g of template (CTAB) and 0.6 g of organic ligand (0.4 g of terephthalic acid and 0.2 g of triethylenediamine) into a beaker containing an organic solvent (DMF), and performing ultrasonication at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template is 50 g / L, and the content of the organic ligand is 38 g / L);

[0131] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.86:1.66), placed in an oven, and reacted at 110° C. for 16 hours. After the reaction is completed, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 60 kPa for 4 hours to obtain a multi-level porous MOFs material;

[0132] (4) Add 0.2 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 40 g / L), place 2 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.1), immerse at 50°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A6.

[0133] Example 7

[0134] The method of Example 1 was implemented, except that the phase change material used was n-octadecane, to obtain a multi-level porous MOFs-based composite phase change material A7.

[0135] Example 8

[0136] The method of Example 2 was implemented, except that the phase change material used was n-octadecane, to obtain a multi-level porous MOFs-based composite phase change material A8.

[0137] Example 9

[0138] The method of Example 3 was implemented, except that the phase change material used was n-octadecane, to obtain a multi-level porous MOFs-based composite phase change material A9.

[0139] Example 10

[0140] The method of Example 1 was followed, except that the phase change material used was paraffin with a phase change temperature of 45° C., to obtain a multi-level porous MOFs-based composite phase change material A10.

[0141] Embodiment 11

[0142] The method of Example 2 was followed, except that the phase change material used was paraffin with a phase change temperature of 45° C., to obtain a multi-level porous MOFs-based composite phase change material A11.

[0143] Comparative Example 1

[0144] (1) adding 2.8 g of metal salt (copper acetate monohydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0145] (2) 3.8 g of organic ligand (trimellitic acid) was added to a beaker containing an organic solvent (anhydrous ethanol), and ultrasonicated at room temperature to mix the mixture evenly to obtain an organic phase solution (the content of organic ligand was 32 g / L);

[0146] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are added to a reaction bottle (the molar ratio of the metal salt to the organic ligand is 1:1.29), placed in an oil bath, and reacted at 40° C. for 8 h. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 100° C. and an absolute vacuum of 60 kPa for 6 h to obtain MOFs material D1-1;

[0147] (4) Add 0.6 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 60 g / L), place 1.5 g of the MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the MOFs material to the organic phase change material is 1:0.4), immerse at 40°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain MOFs-based composite phase change material D1-2.

[0148] Comparative Example 2

[0149] (1) 3.1 g of metal salt (aluminum chloride hexahydrate) was added to a beaker containing water, and ultrasonicated at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt was 45 g / L);

[0150] (2) adding 3.5 g of an organic ligand (2,5-thiophenedicarboxylic acid) to a beaker containing an organic solvent (DMF), and performing ultrasonication at room temperature to mix the mixture uniformly to obtain an organic phase solution (the content of the organic ligand is 58 g / L);

[0151] (3) adding the metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) into a reaction bottle (the molar ratio of the metal salt organic ligand is 1:1.58), placing the reaction bottle in an oil bath, reacting at 100° C. for 9 h, obtaining a suspension after the reaction is completed, and centrifuging the suspension after cooling to room temperature. The obtained solid is washed twice with anhydrous ethanol, and then the washed solid is placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 60 kPa for 4 h to obtain a MOFs material;

[0152] (4) Add 0.6 g of phase change material (n-octadecane) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of phase change material is 60 g / L), place 2 g of the MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the MOFs material to the organic phase change material is 1:0.3), immerse at 70°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain MOFs-based composite phase change material D2.

[0153] Test Example 1

[0154] The specific surface area, total pore volume, pore size, maximum temperature of the adsorption process, ethane adsorption amount and breakthrough point adsorption rate of A1-A11, B1, D1-1, D1-2 and D2 were measured respectively.

[0155] Testing instrument: BSD-PM2 surface area analyzer produced by Beijing Best Instrument Technology Co., Ltd.

[0156] About 100 mg of powder samples were weighed respectively, and after vacuum degassing at 150°C for 12 h, the corresponding data were obtained by testing with nitrogen as the probe molecule at liquid nitrogen temperature (-196°C);

[0157] Among them, the specific surface area (S BET ) was calculated using the Brunauer-Emmet-Teller (BET) equation, with a relative pressure point range of 0.01 to 0.15, and a correlation coefficient greater than 0.999 and a C value greater than 0. The total pore volume was obtained from the N2 adsorption at a relative pressure of 0.99. The pore size distribution was obtained using the nonlocalized density functional theory (NLDFT) method;

[0158] The multi-component adsorption breakthrough curve analyzer (BSD-MAB) of Best Instrument Technology (Beijing) Co., Ltd. was used to measure the breakthrough adsorption curve of ethane gas for each sample, and the adsorption amount of ethane was calculated; the highest temperature during the adsorption process was measured by the temperature sensor on the analyzer;

[0159] The specific operation process of measuring the penetration curve of ethane gas is as follows: first weigh about 150g of sample and load it into the penetration column, purge it with helium at a flow rate of 300ml / min for 2h to remove the impurity gas on the surface of the sample. Place the penetration column in a 298K constant temperature water bath, and after the test environment is stable, start the penetration experiment, test the ethane penetration adsorption curve (gas flow rate is 900mL / min, ethane concentration is 10%VOL, test temperature and pressure are 25℃ and 5bar respectively), and calculate the adsorption amount;

[0160] The adsorption amount of each component was calculated by the following formula:

[0161]

[0162] Note: This calculation formula takes into account the concentration change caused by the real-time change of the outlet flow rate due to adsorption, which improves the accuracy of calculating the adsorption amount by concentration integral.

[0163] Q n吸附 : The amount of adsorbent adsorbed on adsorbate n (unit: mL)

[0164] Q n入总 : The total flow rate of adsorbate n flowing into the column within the time ΔT (unit: mL)

[0165] Q n出总 : The total flow rate of adsorbate n flowing out of the column within the time ΔT (unit: mL)

[0166] q 总入 : Total gas flow rate through the column inlet (unit: mL / min)

[0167] q 载气 : Carrier gas flow rate (unit: mL / min)

[0168] C n0 : The percentage concentration of adsorbate n at the entrance of the penetration column (%)

[0169] C nt : The percentage concentration of adsorbate n at a certain moment at the outlet of the penetration column (%)

[0170] ΔT: total time from the start to the end of adsorption (unit: s) for the adsorption amount of each component.

[0171] The calculation formula of penetration point adsorption rate is:

[0172]

[0173] Q: The amount of adsorbate n when the adsorbent is penetrated (unit: mL / g)

[0174] t: time when the adsorbent is penetrated (unit: min)

[0175] The results are shown in Table 1 and Figure 1-7 As shown ( Figure 1 is the nitrogen adsorption isotherm of B1; Figure 2 is the pore size distribution range of B1, Figure 3 This is the breakthrough adsorption curve of B1 for ethane. Figure 4 is the pore size distribution range of A1, Figure 5 This is the breakthrough adsorption curve of A1 for ethane. Figure 6 is the breakthrough adsorption curve of A2 for ethane, Figure 7 (a) is the breakthrough adsorption curve of A3 for ethane.

[0176] Table 1

[0177]

[0178] Figure 1 and Figure 2 The nitrogen adsorption isotherm and pore size distribution of B1 are given. It can be seen from the figure that a multi-level porous MOFs material is generated under the action of the template. Figure 2 It can be seen that B1 has micropores, mesopores and macropores at the same time, and the ratio of micropore volume, mesopore volume and macropore volume is 1.76:1.28:1. Table 1 shows the pore structure data, adsorption temperature rise and adsorption capacity of the composite material. Since the phase change material occupies a certain pore volume, the pore volume of A1 is smaller than that of B1 and D1-1. During the ethane adsorption process, the material phase changes and absorbs adsorption heat, so the temperature rise of A1 is the lowest. The lower temperature is conducive to the material adsorbing ethane, so the ethane adsorption capacity of A1 is higher than that of B1 and D1-1.

[0179] Examples 1-6 show that the present method forms a porous MOFs material under the action of a template and can be composited with a phase change material to form a self-controlled temperature adsorption material, and the pore volume of the obtained material is 0.3-0.5 mL / g, and the ethane adsorption capacity is 63-74 mL / g, wherein the temperature rise caused by the adsorption of ethane is 13-16° C. Materials A7 and A8 show that the composite material with the addition of n-octadecane can suppress the adsorption temperature rise through the phase change process, but it has a certain impact on the pore structure of the adsorption material.

[0180] Compared with Example 1 and Comparative Example 1, material A1 is a composite of multi-level porous MOFs and phase change materials, while material D1-2 is a microporous structure, and it is difficult for the phase change material to enter the micropores. Therefore, there are significant differences in the temperature control effect and adsorption performance of the two materials. Since it is difficult for the phase change material to enter the micropores, the structures and performances of D1-1 and D1-2 are basically similar; similarly, it is also difficult for the phase change material in Comparative Example 2 to enter the micropores, so D2 does not have the function of phase change temperature control, and the ethane adsorption capacity of D2 is relatively low.

[0181] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A multi-level porous MOFs-based composite phase change material, characterized in that: The multi-level porous MOFs-based composite phase change material comprises a multi-level porous MOFs material having micropores, mesopores and macropores, and a phase change material loaded in the macropore channels of the multi-level porous MOFs material.

2. The multi-level porous MOFs-based composite phase change material according to claim 1, characterized in that: The ratio of the micropore volume, mesopore volume and macropore volume of the hierarchical MOFs material is 1-4:1-2:1; Preferably, the specific surface area of ​​the multi-level porous MOFs material is 600-1700m 2 / g.

3. The multi-level porous MOFs-based composite phase change material according to claim 1 or 2, characterized in that: The phase change material is selected from one or more of polyols, fatty acids, linear alkanes and paraffins; Preferably, the polyols are polyethylene glycol and / or neopentyl glycol; Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid; Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

4. The method for preparing the multi-level porous MOFs-based composite phase change material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a metal salt with water to obtain a metal salt solution; (2) mixing the template, the organic ligand and the organic solvent to obtain an organic phase solution; (3) mixing the metal salt solution with the organic phase solution, and then reacting, separating the solid and the liquid after the reaction, and washing and activating the obtained solid in sequence to obtain a hierarchical porous MOFs material; (4) Mixing a phase change material with an organic solvent to obtain an organic phase change material solution, and immersing the multi-level porous MOFs material in the organic phase change material solution.

5. The preparation method according to claim 4, characterized in that: In step (1), the metal salt is selected from one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate, zirconium chloride and nickel chloride hexahydrate; Preferably, the content of metal salt in the metal salt solution is 5-50 g / L.

6. The preparation method according to claim 4 or 5, characterized in that: The template agent is selected from one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and N,N,N,N-tetramethylethylenediamine.

7. The preparation method according to claim 4, characterized in that: The organic ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, 2,5-thiophenedicarboxylic acid and triethylenediamine; Preferably, the organic ligand is selected from one or more of 2-aminoterephthalic acid, 2,5-thiophenedicarboxylic acid, trimesic acid, terephthalic acid and triethylenediamine.

8. The preparation method according to claim 4, characterized in that: The organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane; Preferably, the content of the template in the organic phase solution is 10-80 g / L, and the content of the organic ligand is 30-150 g / L.

9. The preparation method according to claim 4, characterized in that: The molar ratio of the metal salt, the template and the organic ligand is 1:0.03-1:1-2.

10. The preparation method according to claim 4, characterized in that: In step (3), the reaction conditions include: temperature of 20-160°C and time of 6-18h; Preferably, the reaction conditions include: temperature of 40-110° C. and time of 8-16 h.

11. The preparation method according to claim 4 or 10, characterized in that: In step (3), the activation conditions include: temperature of 80-180°C, time of 1-24h, and absolute vacuum of 20-80kPa; Preferably, the activation temperature is 100-160° C., and the activation time is 2-6 hours.

12. The preparation method according to claim 4, characterized in that: In step (4), the content of phase change material in the organic phase change material solution is 5-80 g / L; Preferably, the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.05-0.

5.

13. The preparation method according to claim 4 or 12, characterized in that: In step (4), the immersion conditions include: time of 4-7 hours and temperature of 40-70°C.

14. Use of the multi-level porous MOFs-based composite phase change material according to any one of claims 1 to 3 in the adsorption of VOCs.

Citation Information

Patent Citations

  • Adsorption bed layer doped with phase change material

    CN104107619A

  • Method of synthesizing porous ZIF-67 material quickly at constant temperature by using kation template

    CN109369922A

  • Method for preparing hierarchical porous UiO-66 material by using sodium dodecyl sulfonate as template

    CN110105581A

  • Hierarchical pore UiO-66 material as well as preparation method and application thereof

    CN111690144A

  • Hierarchical pore metal organic framework composite phase change material and preparation method thereof

    CN112920778A